Silica Composite Materials for Enhanced Arsenic Adsorption in Water Treatment Applications : A Review - Rizqa Afdhila; Nur Azizah (Journal of Carbazon, 2025)
Arsenic contamination in water is a critical environmental concern due to its high toxicity and persistence, posing serious risks to human health and ecosystems. Adsorption is considered one of the most efficient and cost-effective methods for arsenic removal, especially using composite adsorbents. This study evaluates several silica-based composite adsorbents designed to enhance arsenic removal from aqueous solutions. The composites combine silica with various functional materials, including iron oxide, iron(III) nitrate, iron(III) chloride, manganese, magnesium, activated carbon, and polyamines, aiming to improve adsorption capacity, selectivity, thermal stability, and reusability. Adsorption performance was assessed under varying pH levels, adsorbent dosages, contact times, initial arsenic concentrations, and temperatures. Among the tested materials, the iron oxide loaded silica (IOLS) composite (silica, iron(II) sulfate, and iron(III) chloride) exhibited the highest As(III) adsorption capacity of 82.4 mg/g at pH 7 with 90 minutes contact time. Meanwhile, the ironmanganese oxide incorporated rice husk silica (FMRS-2) composite (silica, iron oxide, and manganese) achieved an As(V) adsorption capacity of 20.3 mg/g at pH 7 after 24 hours, with 100% removal efficiency sustained over four regeneration cycles.